The Relationship of Student Learning Achievement in Engineering Drawings with Software Applications and Building Interior Design at Modeling and Building Information Design Study Program in SMK Negeri 3 Surabaya: learning achievement result, technical drawing, software application - Afrizal Lazuadi , Muhammad; dwi mulyono, wahyu (Universitas Nahdatul Ulama Surabaya, 2022)
Developments in the world of own design allow for increased accuracy and quality, the replacement of manual drawing machines into a digital application that can define what will be built. The research objectives in this article are to (1) determine the level of mastery of learning to draw techniques at SMK Negeri 3 Surabaya, (2) determine the level of learning achievement in the application class with software and building interior design at SMK Negeri 3 Surabaya, and 3) determine the relationship between the level of learning achievement in class engineering drawing subjects and the level of achievement in learning software application subjects. In this research, the research technique is Ex post facto, data is collected through tests and documentation, then each variable is characterized using statistical software, namely SPSS version 26.0 for windows, a prerequisite analysis test is carried out. It was decided to do a test. The researcher observed that students who excel in technical drawing and those who excel in software applications are linked by a correlation score of r count > r table (0.680 > 0.235) between the two variables. The correlation coefficient value of 46% is a contribution to the success of learning engineering drawing on the learning outcomes of software applications and building interior design. For other quantities determined by values not included in this study.